OPINI PUBLIK SEBAGAI DETERMINAN UPAYA INDONESIA DALAM ISU PROTES MALAYSIA TERKAIT REGULASI PENENGGELAMAN KAPAL - Anggreni, Luh Mitha Sari; Sushanti, Sukma; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This research aims to describe how public opinion determines the Indonesian government's public diplomacy efforts in responding to the Malaysian protest issue related to the sinking ship regulation using a qualitative descriptive method. The policy of sinking ships implemented by Indonesia on Malaysian fishing boats crossing Indonesian waters has drawn criticism from the Malaysian public who consider the sinking to be an act of unilateral confrontation from the Indonesian government.  As a result, tensions arise in Indonesia-Malaysia relations, which require responsive efforts from Indonesia to defuse tensions between the two countries.  Therefore, this study uses the concept of public opinion in foreign policy by analyzing how public opinion determines Indonesia's public diplomacy efforts in responding to Malaysian public opinion.  This study finds the answer that public diplomacy carried out by the Indonesian government is the government's response to Malaysian public opinion.   Keywords: Malaysian Public Opinion, Public Diplomacy, Public Opinion in Foreign Policy, Sinking Ship Policy.